2021
DOI: 10.1016/j.cub.2021.04.057
|View full text |Cite|
|
Sign up to set email alerts
|

Abscisic acid signaling activates distinct VND transcription factors to promote xylem differentiation in Arabidopsis

Abstract: Highlights d Water limitation promotes cell-autonomous ABA signaling to affect xylem development d ABA promotes both xylem cell fate change and differentiation rate d These xylem development effects are mediated by distinct VND transcription factors d Root xylem developmental ABA response is evolutionarily conserved among eudicots

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 36 publications
2
62
0
Order By: Relevance
“…These complex developmental processes are extremely sensitive to signals sensing environmental changes ( Chaiwanon et al, 2016 ; Perini et al, 2012 ). For instance, recent findings ( Jang and Choi, 2018 ; Jang et al, 2017 ; Ramachandran et al, 2020 ; 2021 ) have revealed that xylem differentiation within the stele is largely influenced by reduced water availability via JA and ABA signaling.…”
Section: Introductionmentioning
confidence: 99%
“…These complex developmental processes are extremely sensitive to signals sensing environmental changes ( Chaiwanon et al, 2016 ; Perini et al, 2012 ). For instance, recent findings ( Jang and Choi, 2018 ; Jang et al, 2017 ; Ramachandran et al, 2020 ; 2021 ) have revealed that xylem differentiation within the stele is largely influenced by reduced water availability via JA and ABA signaling.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found that ZjVND7 and ZjSMR1 were responsive to ABA with the same expression trend, implying a positive regulatory effect (Supplementary Figure 5). Moreover, the targeted ABRE sequence detected in autotetraploids indicated that the binding of ZjVND7 and ZjSMR1 may occur in response to the accumulation of antimitotic ABA and could further promote differences in vessel differentiation between diploid and autotetraploid plants (Ramachandran et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Xylem gaps are not only observed upon salt stress, but certain genotypes display gaps also under normal conditions, including protoxylem gaps in ga4 (Fig. 3b) and metaxylem gaps upon inhibition of ABA signaling in the endodermis (Ramachandran et al, 2021).…”
Section: Expansins May Be Involved In Della Dependent Xylem Gap Forma...mentioning
confidence: 99%
“…The hormone abscisic acid (ABA) mediates these developmental responses by at least two different mechanisms. Firstly, ABA promotes the production of miR165 in the endodermis (Ramachandran et al, 2018; Bloch et al, 2019; Ramachandran et al, 2021). This miRNA moves into the stele to reduce homeodomain leucine zipper class III (HD-ZIP III) mRNA levels eventually leading to protoxylem formation in place of metaxylem (Carlsbecker et al, 2010; Miyashima et al, 2011).…”
Section: Introductionmentioning
confidence: 99%